Acute and Chronic Sarcoid Arthropathies: Characteristics and Treatments From a Retrospective Nationwide French Study - Cacciatore, Carlotta; Belnou, Pierre; Thietart, Sara; Desthieux, Carole; Versini, Mathilde; Abisror, Noemie; Ottaviani, Sébastien; Cormier, Gregoire; Deroux, Alban; Dellal, Azeddine; Belhomme, Nicolas; Kermanac'H, Nathalie Saidenberg; et al. (Frontiers in Medicine, 2020)
Introduction: We aimed to analyze patients with acute and chronic joint involvements in sarcoidosis. Methods: This is a retrospective multicenter analysis of patients with proven sarcoidosis, as defined by clinical, radiological, and histological criteria, with at least one clinical and/or ultrasonographic synovitis. Results: Thirty-nine patients with sarcoid arthropathy were included, and among them 19 had acute sarcoidosis (Lofgren's syndrome). Joint involvement and DAS44-CRP were not significantly different in acute and chronic sarcoid arthropathies. Acute forms were more frequent than chronic sarcoid arthropathy in Caucasians, without any difference of sex or age between these 2 forms. Joint involvement was frequently more symmetrical in acute than chronic forms (100 vs. 70%; p < 0.05), with a more frequent involvement in wrists and ankles in acute forms, whereas the tender and swollen joint counts and the DAS44-CRP were similar between the 2 groups. Skin lesions were significantly more frequent in patients with acute forms [17 (89%) vs. 5 (25%); p < 0.05] and were erythema nodosum in all patients with Löfgren's syndrome and sarcoid skin lesions in those with chronic sarcoidosis. Among 20 patients with chronic sarcoidosis, treatment was used in 17 (85%) cases, and consisted in NSAIDs alone (n = 5; 25%), steroids alone (n = 5; 25%), hydroxychloroquine (n = 2; 20%), methotrexate (n = 3; 15%), and TNF inhibitors (n = 2; 10%). A complete/partial joint response was noted in 14 (70%) cases with a DAS44-CRP reduction of 2.07 [1.85–2.44] (from 3.13 [2.76–3.42] to 1.06 [0.9–1.17]; p < 0.05). Conclusion: Sarcoid arthropathies have different clinical phenotypes in acute and chronic forms and various treatment regimens such as hydroxychloroquine and methotrexate could be used in chronic forms.